2020
DOI: 10.2147/rru.s249611
|View full text |Cite
|
Sign up to set email alerts
|

<p>Polycystic Ovary Syndrome and Pelvic Floor Dysfunction: A Narrative Review</p>

Abstract: Pelvic floor dysfunction is one of the most common disorders in women that is associated with social and economic consequences. In general, this disorder imposes direct and indirect costs on the economy of various societies. This review aimed to investigate pelvic floor dysfunction in women with polycystic ovary syndrome (PCOS). In this narrative review, the published articles on pelvic floor dysfunction were examined in PubMed, Scopus, Web of Sciences and Google Scholar. We searched for terms related to polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…It is therefore not surprising that the prevalence of infertility in women with PCOS is about 70 to 80% [ 3 ]. PCOS has also been found to increase the risk of miscarriage, anxiety, and depression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that the prevalence of infertility in women with PCOS is about 70 to 80% [ 3 ]. PCOS has also been found to increase the risk of miscarriage, anxiety, and depression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(10) Another research showed that raise in body mass causes over pressure exertion on bladder and pelvic floor muscles as a result urinary problem symptoms are observed in such cases. (11) Obesity plays a vital role is hormonal imbalance and PCOS it is a predisposing factor for PCOS and their consequences effects major body organs for example Urinary system, body's metabolic system reducing weight will cause improvement in condition. (12) Previous study showed that high BMI and PCOS both are involved in causing urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Social stigma is a major factor that puts a stop to the regular health visit of women suffering from PFDs especially in a lower economy country where literacy rate is also less. They gradually undergo distress and are despondent until they are revealing their problems [ 33 ]. The reporting of PFDs related diseases is less documented than actually; it persists in the current scenario especially in the rural population of India.…”
Section: Discussionmentioning
confidence: 99%